PERKEMBANGAN KOTA KECIL MUNTILAN KABUPATEN MAGELANG - Ritohardoyo, Su (Patra Widya: Seri Penerbitan Penelitian Sejarah dan Budaya., 2019)
Gaps still become common condition in small-scale city development studies that so far has less attention. Therefore, this research is aimed to analyze the history of the development of small cities and regional economies; contribution of location factors and their relationship with the development. The study was conducted in the small town of Muntilan, Magelang Regency, Central Java Province using a secondary data analysis research method. The unit of analysis is a census researched village. Data analysis used were quantitative and qualitative techniques.